The Rationale of Economics and Law in the Aftermath of the Crisis: A Lesson from Michel Foucault. (6th December 2016) - De Lucia, Luca
Abstract : Economic and financial crisis – Institutional response and constitutional changes in the area of economic governance – Relationship between the European Union and the member states – Interpretation – Two concepts elaborated by Michel Foucault – 'Pastorship' and 'Discipline' – The deep sense of the new techniques of government in this area – The role of the Court of Justice – The position of national judges.